EMPOWERED VOICES: UNMARRIED WOMEN’S PERSPECTIVE ON ‘PERAWAN TUA’ - Maylon, Zephyr Sumayyah; Primadini, Intan (Lingkar Studi Komunikasi (LISKI), 2025)
The deep-rooted patriarchal culture in Indonesia makes women seen as submissive and inferior to men, so they often receive unfair treatment in the society. Along with the increasing awareness of gender equality, women are starting to dare to choose the path of life they want, including in terms of marital status. The phenomenon of postponing marriage is increasingly widespread because of the awareness of what women will face when getting married in an environment with a patriarchal culture that is still inherent in the society. This can be seen through the increase in the number of unmarried women and the shift in the average age of marriage for women in Indonesia. Ironically, the result of patriarchal culture is still very much embedded in society, making unmarried women obtain a negative stigma from society, which is "perawan tua" as one of them. The purpose of this research is to find out how women who have never been married interpret the term "perawan tua" by society. This research uses a qualitative approach with phenomenological methods analyzed through interpretative phenomenological analysis (IPA) techniques. Interview techniques were used in collecting data for this study and analyzed using the data analysis technique by Smith et al. (2009). The results showed that unmarried women interpreted the term "perawan tua" as negative. However, participants did not internalize the term into themselves.